Pengembangan Soal Matematika Terintegasi Nilai Keislaman Al Mawarits pada Materi Pecahan - Dedyerianto, Dedyerianto; Boy, La; Riza, Muhammad; Halistin, Halistin; Riansyah, Firman (Institut Agama Islam Negeri Kendari, 2024)
This research aims to generate integrated mathematics questions aligned with the Islamic values at al mawarits, enabling an examination of the correlation between fraction material in mathematics and the knowledge of mawarits. The research type employed is development utilizing the Teesmer model, consisting of four development stages: the preliminary stage (preparation), the self-evaluation stage (analysis and design), the prototyping stage (validation, revision, evaluation), and the field test stage. The research was conducted at a private junior high school. The results of this study indicate in terms of question difficulty (1 difficult, 6 moderate, and 3 easy questions). For item discrimination, 2 questions are very good, 6 questions are good, and 1 question is moderate. Moreover, regarding the validity level, the developed integrated mathematics questions with Islamic values of al mawarits obtained a validity score of 0.90 and a reliability score of 0.92, indicating that the developed questions are reliable.